LATE OLIGOCENE-EARLY MIOCENE INITIATION OF SHORTENING IN THE SOUTHWESTERN CHINESE TIAN SHAN: IMPLICATIONS FOR NEOGENE SHORTENING RATE VARIATIONS - Sobel E.R.; Chen J.; Heermance R.V. (My University, 2006)
The Cenozoic Tian Shan is one of the preeminent examples of an intracontinental orogen. However, there remains a significant controversy over when deformation related to the India-Asia collision commenced and therefore how shortening within the mountains has been partitioned over time. One approach has been to look at the modern shortening rate as measured by geodetic studies, combined with estimates of the total shortening across the range and extrapolate backwards. This approach suggests that the onset of range construction was ca. 10 Ma [K.Y. Abdrakhmatov, S.A. Aldazhanov, B.H. Hager, M.W. Hamburger, T.A. Herring, K.B. Kalabaev, K.B. Kalabayev, V.I. Makarov, P. Molnar, S.V. Panasyuk, M.T. Prilepin, R.E. Reilinger, I.S. Sadybakasov, B.J. Souter, Y.A. Trapeznikov, V.Y. Tsurkov, A.V. Zubovich, Relatively recent construction of the Tien Shan inferred from GPS measurements of present-day crustal deformation rates, Nature 384 (6608) (1996) 450-453]. An alternate method is to determine the age of the onset of exhumation using thermochronology. We present 19 new apatite fission-track (AFT) results from the southwestern Chinese portion of the belt; this region represents the first area exhumed during the late Tertiary along a transect at ca. 76°E. Exhumation commenced at the Oligocene-Miocene boundary (~ 24 Ma) along the Maidan and Muziduke thrusts, which bound the southern side of the Kokshaal range. Subsequently, deformation propagated ca. 20 km south to the Kashi basin-bounding thrust (KBT), which was exhumed by no earlier than 18.9 ± 3.3 Ma. Three detrital AFT samples from Plio-Pleistocene strata deposited ca. 20 km farther south contain fission track grain age peaks that young monotonically upwards from 20.9 + 7.0/- 5.3 Ma to 15.9 + 5.4/- 4.0 Ma with a fairly constant lag time of 16 to 18 Ma. These ages, combined with structural data, suggest that both the hanging wall and the footwall of the KBT experienced a renewed episode of exhumation during the latest Cenozoic. The discrepancy between the Late Oligocene-Miocene initiation of significant exhumation shown herein and the 10 Ma initiation estimate from geodesy suggests that the Tian Shan has undergone a complex Late Cenozoic shortening history. Assuming that the present shortening rate could account for the total amount of Cenozoic shortening in 10 Ma and realizing that shortening initiated at least 15 Myr earlier, we conclude that the shortening rate must have varied over time, possibly in pulsed-southward migrating events, and that the present rate may not reflect the average rate since initiation of range uplift. © 2006 Elsevier B.V. All rights reserved.
Keywords: CENOZOIC; DEFORMATION; FISSION TRACK; THERMOCHRONOLOGY; TIAN SHAN; Кайнозой::Палеоген::Олигоцен; Кайнозой::Неоген::Миоцен